Analisis Tingkat Kematangan Sistem Pemerintahan Berbasis Elektronik (SPBE) pada Pemerintah Provinsi Sulawesi Selatan - Hidayah, Endang Sri; Almadani, Muzzaman (Jurnal Teknologi dan Komunikasi Pemerintahan, 2022)
Abstract The application of Information Technology is currently very influential in people's lives with the aim of achieving a world-class bureaucracy where governance is more effective, efficient, transparent, and accountable and the quality of public services is easier, faster, and affordable. One of them is the implementation of the SPBE (Electronic-Based Government System). The South Sulawesi Provincial Government implements the development of E-Government by implementing SPBE in its work process. The implementation of SPBE has had a great impact on the Provincial Government which is the benchmark for Regional Apparatuses, as well as during the COVID-19 Pandemic which required civil servants to work from home (work from home). This research is an observational study that combines field data with library data and is equipped with an interview study to obtain maximum results. In accordance with the research objectives, namely to identify the maturity level of information technology in South Sulawesi Province. The results of the writing show that the SPBE maturity level of the South Sulawesi Provincial Government has an index value of 2.05 with the predicate "Enough". Some aspects of the SPBE assessment are represented as having a very low contribution value which results in a lack of SPBE index scores for the South Sulawesi Provincial Government. One of them is the ICT audit aspect, with three assessment indicators (indicator 29 implementation of SPBE infrastructure audit, indicator 30 implementation of SPBE application audit and indicator 31 implementation of SPBE security audit). Each indicator in the ICT audit aspect has the same weakness, namely that a representative assessment cannot be carried out because there is no supporting evidence that explains it is in accordance with the specified criteria, so that the lowest score is obtained. Recommendations for improvement are to increase the evaluation value on the three indicators in the hope of improving the business process of implementing SPBE and the quality of work in the South Sulawesi Provincial Government that is effective, efficient, and productive as well as aligning the SPBE architecture and the SPBE roadmap from the central government. Keywords: Analyst, SPBE Abstrak Penerapan Teknologi Informasi saat ini sangat berpengaruh bagi kehidupan masyarakat dengan tujuan mencapai birokrasi berkelas dunia dimana tata kelola pemerintahan semakin efektif, efisien, transparan, dan akuntabel serta kualitas pelayanan publik semakin mudah, cepat, dan terjangkau. Salah satunya dengan penerapan (Sistem Pemerintahan Berbasis Elektronik) SPBE. Pemerintah Provinsi Sulawesi Selatan menerapkan pengembangan E-Government dengan pelaksanaan SPBE pada proses kerjanya. Penerapan SPBE sangat berpengaruh pada Pemerintah Provinsi yang menjadi tolak ukur Perangkat Daerah, juga saat terjadinya Pandemi COVID-19 yang mengharuskan PNS bekerja dari rumah (work from home). Penelitian ini merupakan Studi Observasi yang memadukan antara data lapangan dengan data pustaka dan dilengkapi dengan studi wawancara untuk memperoleh hasil yang maksimal. Sesuai dengan tujuan penelitian yaitu untuk mengidentifikasi tingkat kematangan teknologi informasi di Provinsi Sulawesi Selatan. Hasil dari penulisan menunjukan tingkat kematangan SPBE Pemerintah Provinsi Sulawesi Selatan memperoleh nilai indeks sebesar 2.05 dengan predikat “Cukup”. Beberapa aspek penilaian SPBE direpresentasikan memiliki nilai kontribusi sangat rendah yang mengakibatkan kurangnya nilai indeks SPBE Pemerintah Provinsi Sulawesi Selatan. Salah satunya yakni aspek audit TIK, dengan tiga indikator penilainya (indikator 29 Pelaksanaan audit infrastruktur SPBE, indikator 30 pelaksanaan audit aplikasi SPBE dan indikator 31 pelaksanaan audit keamanan SPBE). Masing-masing indikator pada aspek audit TIK memiliki kelemahan yang sama yakni belum bisa dilakukan asesmen secara representatif karena tidak ada satupun bukti dukung yang menjelaskan sesuai dengan kriteria yang ditentukan, sehingga diperoleh nilai yang paling rendah. Rekomendasi perbaikan untuk meningkatkan nilai evaluasi pada ketiga indikator dengan harapan dapat memperbaiki proses bisnis penerapan SPBE dan kualitas kerja pada Pemerintah Provinsi Sulawesi Selatan yang efektif, efisien, dan produktif serta menyelaraskan arsitektur SPBE dan peta jalan SPBE dari pemerintah pusat. Kata Kunci: Analis, SPBE